Evolution of the tasks of the Common Agricultural Policy – the past, the present and the future - Jurcewicz, Alina; Włodarczyk, Beata; Tomkiewicz, Elżbieta (Przegląd Prawa Rolnego, 2024)
The aim of this article is to present the tasks of the Common Agricultural Policy. The historical context and conditions of the treaty provisions defining the tasks of this policy are presented. Against this background, the evolution of the CAP from the past, through the present and the future is characterised. The conclusions state, among other things, that the CAP will remain one of the most important sectoral policies of the EU in the future, although there is a visible tendency to reduce expenditure on agriculture. The need to subsidise agriculture heavily is no longer justified and socially legitimised as before. The agricultural sector will undoubtedly become subject to processes leading to the use of innovative farming methods. Consequently, the interpretation of the tasks of the CAP should continue to take place in the light of the development of agriculture and the economy as a whole.